2021
DOI: 10.1007/s12134-021-00899-x
|View full text |Cite
|
Sign up to set email alerts
|

The Life Satisfaction of Immigrants in Canada: Does Time Since Arrival Matter more than Income?

Abstract: The subjective life satisfaction of individuals reveals valuable information about the overall well-being of a society. Furthermore, large international migration flows have led to the importance of studying the life satisfaction of immigrants within host countries, including Canada. This study uses secondary data from the 2013 Canadian General Social Survey, Cycle 27, to assess the life satisfaction of immigrants in Canada compared to Canadian-born individuals, and to determine the overall impact of immigrant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 53 publications
0
2
1
Order By: Relevance
“…Safi (2010) provides the most comprehensive international evidence on this negative association: using data from the ESS, immigrants reported lower levels of LS in all of the 13 European countries included in the study, with LS being lowest among immigrants who arrived in the host country 5-10 years ago. Contrary to our findings, time since migration did not have a significant effect on immigrants' LS in Canada (Monteiro and Haan 2021), but the same study found income to be a predictor of their LS. Focusing on LS and life evaluation in a pooled sample of European and Anglo-Saxon countries that were included in the Gallup World Poll, Olgiati et al (2013) found that higher incomes are associated with higher well-being outcomes for immigrants in only a few countries, suggesting that other factors are important determinants of migrants' LS.…”
Section: Ls and Migrationcontrasting
confidence: 99%
“…Safi (2010) provides the most comprehensive international evidence on this negative association: using data from the ESS, immigrants reported lower levels of LS in all of the 13 European countries included in the study, with LS being lowest among immigrants who arrived in the host country 5-10 years ago. Contrary to our findings, time since migration did not have a significant effect on immigrants' LS in Canada (Monteiro and Haan 2021), but the same study found income to be a predictor of their LS. Focusing on LS and life evaluation in a pooled sample of European and Anglo-Saxon countries that were included in the Gallup World Poll, Olgiati et al (2013) found that higher incomes are associated with higher well-being outcomes for immigrants in only a few countries, suggesting that other factors are important determinants of migrants' LS.…”
Section: Ls and Migrationcontrasting
confidence: 99%
“…Nonetheless, they are a heterogeneous population: They come from different origin countries, have different cultural backgrounds, and vary in their ability to form networks and integrate in the host country (Ciobanu et al 2017;King et al 2017). While existing research often groups migrants from different countries of origin (Arpino/de Valk 2018;Calvo et al 2017;Monteiro/Haan 2022), we focus on a very specifi c migration stream. This article thus aims to contribute to the scarce literature on older migrant well-being by 1) examining the difference in life satisfaction levels between three groups of older adults: Italian migrants living in Switzerland, Swiss natives, and Italian stayers living in Italy, and 2) analyzing the differences in the determinants of life satisfaction across these three groups.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, some studies revealed that the disparity between native-born Europeans and migrants does not diminish with time or across generations (Amit 2010;Kogan et al 2018;Safi 2010), while others found that this difference does diminish over generations (Arpino/de Valk 2018). Furthermore, Monteiro and Haan's (2022) research on migrants in Canada found no difference between the life satisfaction of migrants and that of Canadian natives when controlling for sociodemographic variables, and year of arrival in Canada has no signifi cant effect on life satisfaction. The implications of having a migration background are therefore still unclear, and migration may infl uence life satisfaction differently for different populations.…”
Section: The Migrant-native Comparisonmentioning
confidence: 99%